Investor-State Dispute Settlement and National Courts Current Framework and Reform Options. - Kaufmann-Kohler, Gabrielle (European Yearbook of International Economic Law; Special Issue, 2020)
This open access book examines the multiple intersections between national and international courts in the field of investment protection, and suggests possible modes for regulating future jurisdictional interactions between domestic courts and international tribunals. The current system of foreign investment protection consists of more than 3,000 international investment agreements (IIAs), most of which provide for investment arbitration as the forum for the resolution of disputes between foreign investors and host States. However, national courts also have jurisdiction over certain matters involving cross-border investments. International investment tribunals and national courts thus interact in a number of ways, which range from harmonious co-existence to reinforcing complementation, reciprocal supervision and, occasionally, competition and discord. The book maps this complex relationship between dispute settlement bodies in the current investment treaty context and assesses the potential role of domestic courts in future treaty frameworks that could emerge from the States' current efforts to reform the system. The book concludes that, in certain areas of interaction between domestic courts and international investment tribunals, the "division of labor" between the two bodies is not always optimal, producing inefficiencies that burden the system as a whole. In these areas, there is a need for improvement by introducing a more fruitful allocation of tasks between domestic and international courts and tribunals - whatever form(s) the international mechanism for the settlement of investment disputes may take. Given its scope, the book contributes not only to legal analysis, but also to the policy reflections that are needed for ongoing efforts to reform investor-State dispute settlement.